2016
DOI: 10.1161/strokeaha.115.010898
|View full text |Cite
|
Sign up to set email alerts
|

An International Standard Set of Patient-Centered Outcome Measures After Stroke

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
169
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(183 citation statements)
references
References 30 publications
2
169
1
3
Order By: Relevance
“…29 Registry expertise and experience shared across countries could stimulate further development in how to use comprehensive process and results data in improving, for example, stroke care. 30 In Sweden, one of the limitations of registries such as Riksstroke is evidently the burden of registering data. 29 This is most likely reflected in that merely 65% of the Riksstroke respondents considered the gain from partaking in the registry, justifying the resources spent on working with it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Registry expertise and experience shared across countries could stimulate further development in how to use comprehensive process and results data in improving, for example, stroke care. 30 In Sweden, one of the limitations of registries such as Riksstroke is evidently the burden of registering data. 29 This is most likely reflected in that merely 65% of the Riksstroke respondents considered the gain from partaking in the registry, justifying the resources spent on working with it.…”
Section: Discussionmentioning
confidence: 99%
“…The following indexes, serving as independent variables, were constructed to capture: Support from Outer Setting; Management Request for Registry Data; Management Involvement in Registry-based Quality Improvement; Data Quality and Usefulness, and Resources. In addition, a number of single questions (items8,24,28,29,30,31 and 46) were included as independent variables comprising: the unit's local results; support from the local department and the registry; simplicity of retrieving data from the registry and explaining the results to colleagues and managers; motivation and colleagues' interest in Riksstroke data.Validation of indexesA factor analysis was conducted using SPSS V.23 to validate that our indexes contained relevantly grouped individual items. The factors were first extracted using direct oblimin rotation.…”
mentioning
confidence: 99%
“…A previous review included studies up to 2007, 3 so we reviewed studies from 2007 onwards that examined sex differences in patient reported outcome measures (PROMs) at ≤12 months after stroke, including activity limitations, HRQoL, participation restriction, impaired cognition, and mood. 6 Full results tables are shown in the online-only Data Supplement. …”
mentioning
confidence: 99%
“…31 Laboratory-based tests of motor gains may be standardized, but do not inherently reflect what is actually performed in the real world or reflect patient-centered outcome measurements. 32 Studies of self-report instruments about participation, within the definition of the International Classification of Functioning, Disability and Health, show that available tools meet very limited success. 33 The need here is great.…”
Section: The Problemsmentioning
confidence: 99%